Pengembangan Model Pembelajaran Berbasis TGT Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Terkait Nilai-Nilai Qada dan Qadar - Adilla, Raisa; J, Jasiah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses the development of a Teams Game Tournament (TGT) based learning model to improve students' critical thinking skills in understanding the values of qada and qadar. In the digital era, Islamic religious education (PAI) faces challenges in conveying abstract concepts that are often difficult for students to understand. This research aims to create an interactive and collaborative learning environment by applying the TGT model, which encourages students to actively participate and think critically. The research method used is a qualitative approach using observation, interviews and phenomenological analysis to understand how students internalize these values. The research results show that the use of the TGT model is able to increase student involvement, as well as their critical thinking skills in applying the concepts of qada and qadar in everyday life. Through group discussions and competitions, students not only understand the material better, but can also apply it practically. The conclusion of this research emphasizes the importance of innovation in learning methods to shape the character of students who think critically and have faith. It is hoped that the TGT model can be an effective alternative in PAI education in the future.